The concept of scientific articles and implications for the visibility of academicians - Anuar, Faizul Nizar; Nordin, Mohd Norazmi; Tan, Say Peng; Abbas, Mohd Saleh (Kohat University of Science and Technology, Institute of Information Technology, 2024)
Academic articles or scholarly articles are a type of writing that is produced with the use of knowledge and a summary of some specific subject matters. This scientific article is the result of an empirical analysis, the discovery of certain ideas and a precise analysis of the field of study. The results of scientific articles are usually published in various types and in various platforms. Scientific publication is a process of disseminating research results, ideas, or new discoveries to the public scientifically through various types of media, such as scientific journals, conferences, monograph papers, policy papers, books, and others. The main purpose of this scientific publication is to share findings and new knowledge with experts in the same field or the community in general. The process of publishing academic materials like this requires some basic things such as reliability analysis, refereeing and even processing before a paper is published for general reading. All the processes involved in the publication of academic materials are very important to determine the quality of the paper and ensure that the knowledge presented is not deviated from the track.